Elevated CO2 not increased temperature has specific effects on soil nematode community either with planting of transgenic Bt rice or non-Bt rice - Song, Yingying; Liu, Jiawen; Chen, Fajun (PeerJ, 2020)
Background Transgenic Bt rice has not been approved for commercial cultivation because of the fierce public debate on food safety, biosafety regulation and ecological risk. Meanwhile, the concentration of CO2 and temperature in the atmosphere, as important environmental factors affecting the persistence of exogenous Bt protein, have increased. Elevated CO2, increased temperature, the planting of transgenic Bt rice and their interactions may further influence the structure and complexity of soil food web. However, the effects of transgenic Bt rice planting on soil organism remain largely unexplored before its commercial production especially under global climate change. Methods Here, we assessed the influences of transgenic Bt rice (cv. HH with fused Cry1Ab/Cry1Ac in contrast to its parental line of non-Bt rice cv. MH63) on soil nematode communities under the conditions of elevated CO2 concentration and increased temperature for 2 years of 2016 and 2017 in open-top chambers located in Ningjin County, Shandong Province of China. Results Elevated CO2 concentration remarkably increased the abundance of fungivores and significantly decreased their nematode channel ratio (NCR) and enrichment index (EI) irrespective of rice variety (transgenic Bt rice or non-Bt rice) or temperature (normal temperature or increased temperature). Additionally, rice variety and temperature did not significantly change soil nematode composition, abundance and ecological indices (including total maturity index (∑MI), Shannon diversity (H′), structure index (SI), NCR and EI). However, apparent seasonal changes were observed in theses aforementioned variables. Discussion These results suggested that atmospheric CO2 concentration but not temperature or rice variety has great impacts on soil nematode community, especially fungivores.
Keywords: Global climate change; Transgenic Bt crop; Soil fauna; Trophic group; Ecological index